Arabic Learning Management; Methodological And Psychological Perspective - Syamsuddin, Naidin; Garancang, Sabaruddin; Kasim, Amrah; Haniah, Haniah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the planning, implementation and evaluation of learning Arabic from a methodological and psychological perspective at UPT SMA Palopo City. This research is a type of field research whose study is descriptive-qualitative to reveal the meaning behind the reality of learning Arabic at UPT SMA Palopo City. The data collection method was through interviews which were then analyzed qualitatively using data reduction, data presentation and research conclusions. The results showed that: Learning Arabic at UPT SMA Palopo City includes three processes, namely: 1) The planning process for learning Arabic at UPT SMA Palopo City includes making syllabus, lesson plans and learning media to be used; 2) Implementation, learning Arabic at UPT SMA Palopo City includes initial activities, delivery of material and closing. Implementing learning Arabic at UPT SMA Palopo City could be more optimal; 3) Evaluation, which includes evaluation of students in the form of semester exams, assignments and so on.